Detection of mercury ions using unmodified silver nanoparticles as colorimetric indicator. (April 2020) - Handayani, W; Pratiwi, N I; Imawan, C
Abstract: Detection of the heavy metal presence in an environment requires a rapid and facile method. Silver nanoparticles (AgNPs) can be develop as colorimetric indicator related to their unique characteristics of its LPSR properties. In this research, biosynthetically AgNPs using Diospyros discolor leaf extract used as a colorimetric indicator for detecting Hg 2+ ions. The solution color changes that occur when detecting the analyte was observed. The characterization was performed using a UV-Vis spectrophotometer to study changes in the LSPR spectrum of silver nanoparticles when detecting the presence of Hg 2+ ions. In addition, the image analysis from Transmission Electron Microscope (TEM) was carried out to determine the shape and size of the AgNPs. The results obtained indicate that there was a tendency for the solution color change from brown to light-brown when AgNPs interact with Hg 2+ ions at 500-1000 mg. L −1 . This result showed that without modification the biosynthesized AgNPs tend to be selective and sensitive to the presence of Hg 2+ ions.